2010
DOI: 10.1002/poc.1660
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effect on the UV spectra of p‐disubstituted compounds XPh(CHCHPh)nY (n = 0, 1, 2)

Abstract: Three parameters, ${\rm \sigma }_{\rm CC}^{\rm ex} $, ${\rm \sigma }_{\rm CC}^{\rm ex} ({\rm XY)}$ and $\upsilon_{{\rm max,}\,{\rm parent}} $, are developed to express the substituent effect and the effect of the parent molecular structure of p‐disubstituted compounds XPh(CHCHPh)nY (n = 0, 1, 2). The investigated result shows a good correlation between the UV absorption wavenumbers (υmax) and the three parameters for a diverse set of title compounds, and the correlation equation can be used to predict the UV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“… The σCC)(pex value of Et was taken from ref . the σCC)(pex value of PhO was calculated according to the method of ref .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… The σCC)(pex value of Et was taken from ref . the σCC)(pex value of PhO was calculated according to the method of ref .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cao C. et al . proposed a new excited‐state substituent parameter, σCCex, and recommended the single‐parameter equation (σCCex) or the dual‐parameter equation ( σ p and σCCex) to correlate the UV absorption wavenumbers ( υ max ) of compounds with monosubstituent changed, and then he and co‐workers use this excited‐state substituent parameter to study successfully the UV absorption wavenumbers of compounds with disubstituent changed, as 1,4‐disubstituted benzenes, 4,4'‐disubstituted stilbenes and 4,4'‐disubstituted N‐benzylidenebenzenamines, etc.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…If the 4,4'-disubstituted stilbene derivatives is to be used as optical materials, the effects of substituent and solvent on their UV absorption energy must be known. In author's recent works [16][17][18], the excited-state substituent parameter ex CC  was proposed to scale the effect of intramolecular substituent effect. It is found that the energy of UV absorption max wavelengths of trans-4,4'-disubstituted stilbene derivatives (XPhCH=CHPhY) can be correlated well with two parameters in a given solvent, the sum of ex CC  of substituents X and Y and the interaction between substituents X and Y, ex CC  (X) ex CC  (Y), in which the correlation result using parameter ex CC  is better than that of using polar substituent constant  x or spin-delocalization substituent constant  • [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…of XSBY in a given solventFrom our previous studies[18], it was known that the energy of UV absorption max wavelengths of 4,4'-disubstituted stilbenes in ethanol has a good correlation with the ex CC  of substituents X and Y. Thus, we also attempt to correlate the energy of UV absorption max wavelengths (wavenumbers max  ) of XSBY with two parameters…”
mentioning
confidence: 97%